간호대학생의 인권의식에 영향을 미치는 요인 - 홍선우(Sun-Woo Hong); 김지수(Ji-Soo Kim); 현혜진(Hye-Jin Hyun) (한국콘텐츠학회 논문지, 11(6), 2011)
This study was done to identify awareness of human rights in nursing students, and to evaluate the factors affecting human rights for nursing students. A cross-sectional design was used, with a convenience sample of 440 nursing students from two university in Incheon and Kangwon province. The score for right consciousness was much higher than duty consciousness inherent in human rights. The predicting factor for human rights was mother's rearing attitude in terms of autonomy and this factor explained 7.6% of human rights for nursing students. There was a significant difference on human rights for nursing students according to age and awareness of human rights were related to perceived parents' rearing attitude, self-esteem, psychological home environment. 본 연구에서는 간호대학생의 인권의식을 파악하고 여기에 영향을 미치는 요인을 확인하여 미래 의료현장 전문가로서의 인간 존중에 대한 가치관을 분석하고 함양할 수 있는 방안을 모색하고자 한다. 본 연구를 위해 인천, 강원 지역의 대학교에 재학 중인 간호학과 학생을 대상으로 구조화된 설문지를 배포하여 자료를 수집하였으며 최종 440부를 분석하였다. 분석 결과 간호대학생의 인권의식은 의무적 측면보다 권리적 측면이 더 높게 나타났다. 그리고 인권의식에 영향을 미치는 유의한 요인으로는 어머니의 자율-통제 양육태도였고(p< .001), 어머니의 자율-통제 양육태도는 인권의식을 7.6%설명하는 것으로 나타났다. 또한 간호대학생의 인권의식은 연령에 따라 유의한 차이가 있었으며, 부모의 양육태도, 자아존중감, 심리적환경과는 유의한 상관관계를 나타냈다.